EFEKTIFITAS GERAK DAN LAGU “PERGI KE SEKOLAH” DALAM MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA 5–6 TAHUN - Mittha ratistiningtyas (Jurnal Tata Kelola Pendidikan, 2021)
The purpose of this study was to determine how effective the motion and song "Going To School" in improving the language skills of children aged 5-6 years in TK Pertiwi Banaran Kab. Nganjuk This research is a quantitative study with a pre-experimental design method showing that the motion and the song "Going to School" are effective for stimulating language skills of children aged 5-6 years in group B in TK Pertiwi Banaran Kab. Nganjuk The number of samples in this study were 21 children. Pretest results with an average value of 9.76, a maximum value of 14, and a minimum value of 5. While posttest results with an average value of 14.14, a maximum value of 20, and a minimum value of 4. Results of data analysis using Paired Test Sample T-Test with df = 20 shows a t table of 2.085 and a t-test value of 12.112. This shows t arithmetic from the t table value so that the motion and the song "Go to School" are effective in stimulating language skills of children aged 5-6 years.